1994
DOI: 10.1002/pca.2800050304
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the natural deuterium distribution in glucose from plants having different photosynthetic pathways

Abstract: The site-specific natural isotope fractionation of hydrogen in glucose was investigated by nuclear magnetic resonance spectroscopy (SNIF-NMR). Several glucose samples obtained from plants undergoing either C, (potato, barley, sunflower, wheat) or C4 (maize, sorghum) photosynthetic metabolism were investigated. Since the glucose molecule is not suitable for direct SNIF-NMR analysis, several kinds of derivatives were synthesized. Three clusters of isotopomers were identified in glucose penta-acetate which is ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 20 publications
3
18
0
Order By: Relevance
“…This pattern is much less pronounced in bean endosperm starch, but deviations from a random distribution are still approximately 20%. As far as a comparison is possible, our results agree qualitatively with the results by Martin et al (1986) and Zhang et al (1994). The most striking effect in the spectra is the apparent depletion by approximately 40% of C(2)‐D of chloroplastic starch relative to sucrose or endosperm starch.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This pattern is much less pronounced in bean endosperm starch, but deviations from a random distribution are still approximately 20%. As far as a comparison is possible, our results agree qualitatively with the results by Martin et al (1986) and Zhang et al (1994). The most striking effect in the spectra is the apparent depletion by approximately 40% of C(2)‐D of chloroplastic starch relative to sucrose or endosperm starch.…”
Section: Discussionsupporting
confidence: 90%
“…Derivatives of glucose have to be synthesized because the deuterium NMR spectra of glucose show poor resolution. Intramolecular D distributions of glucose were measured using deuterium NMR and were found to be non‐random (Martin et al 1986; Zhang et al 1994). However, in published derivatization procedures (Martin et al 1986; Williams et al 1993), at least two glucose derivatives have to be synthesized to measure the deuterium abundance of all seven carbon‐bound deuterium atoms, and gram amounts of sample are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Although photorespiration leads to C loss, 3-phosphoglycerate (3-PGA) is formed after both carboxylation and oxygenation, but with differing stoichiometries and along differing paths. Numerous observations have shown that synthesis of a compound via different pathways induces different isotopomer distributions (18,19,(28)(29)(30)(31)(32). No exception to this rule has been observed, and it agrees with the theory of isotope effects.…”
Section: /D6supporting
confidence: 81%
“…The same must be true for other intermediates and final products. So, for example, although the Calvin cycle itself comprises only a sole reduction step, the glyceraldehyde phosphate dehydrogenase (GAPDH) reaction, glucose from different plants [174] and from different compartments within the same plant [175] has, depending on metabolic conditions, a slightly different and variable 2 H pattern of the C-bound hydrogen atoms. Details must be due to the complexity of sugar metabolism, the overlap of synthesis, glycolysis and gluconeogenesis.…”
Section: Key Reactions Metabolic Pathways and Metabolite Fluxes Respmentioning
confidence: 99%